Hubungan Kecerdasan Fluida dengan Kontrol Diri pada Mahasiswa Institut Teknologi Sumatera - Darmawan, Andy; Wulandari, Putri; Nurhayu, Winati (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Fluid intelligence is the ability to think quickl and flexibly in solving new problems without relying on past experiences. Meanwhile, self-control is the ability to carry out necessary tasks and resist unwanted and unnecessary temptations. Students, as individuals transitioning into adulthood, may have unique self-control and fluid intelligence due to ongoing brain development. This study aims to analyze the relationship between fluid intelligence and self-control among students at Sumatra Institute of Technology. The research method used in this study involved interviews using the Baddeley Reasoning Test and self-control Scale with 161 respondents, consisting of 73 males and 88 females. The results of the study indicate that there was no significant relationship between fluid intelligence and self-control. One factor that may explain higher fluid intelligence in males is that they are often required to make decisions. Additionally, higher self-control in females may be attributed to societal expectations of more normative behavior for women.